The Implementation of ICAO and Civil Aviation Regulation in Vocational Higher Education - Widiyanto, Saptandri (Proceeding of International Conference of Advanced Transportation, Engineering, and Applied Social Science, 2023)
The study focuses on the implementation of ICAO and Civil Aviation Regulations in vocational higher education classrooms by using observation and interviews. This study makes an important contribution to the understanding of the importance of compliance with ICAO and civil aviation regulations in vocational higher education. The results of this study identified the stages of implementing ICAO and civil aviation regulations. Additionally, the study also reveals best practices that can be adopted by educational institutions to ensure full compliance with ICAO and civil aviation regulations. This study serves as a basis for educational institutions to improve curricula, teaching methods and practical training to ensure that their graduates understand and comply with aviation security and safety standards set by ICAO and civil aviation regulations.